2015
DOI: 10.1260/1475-472x.14.5-6.883
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustics of Darrieus Wind Turbine

Abstract: The objective of this paper is to validate two different numerical methods for noise prediction of the H-Darrieus wind turbine using a complementary approach consisting of experimental measurements and numerical simulations. The acoustic measurements of a model scale rotor were performed in an anechoic wind tunnel. This data is the basis for the validation of the computational aeroacoustic simulations. Thereby, we have applied two different numerical schemes for noise prediction using hybrid methods. As usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…The first wind tunnel research programmes for VAWT applications were used to obtain the turbine's characteristic operating curves as the basis for machine design under various steady wind conditions. For example, Mazarbhuiya et al 155 investigated a turbine's performance using different asymmetric blades with a focus on the influence of blade aspect ratio whilst specialist facilities enable the breadth of experimentation to be expanded as exemplified by Weber et al 156 who studied turbine noise in the wind tunnel with a 1/2-inch free-field microphones. They showed that the main sources of the H-Darrieus sound pressure field were the separation-stall and the blade vortex interaction.…”
Section: Traditional Wind Tunnel Measurementmentioning
confidence: 99%
“…The first wind tunnel research programmes for VAWT applications were used to obtain the turbine's characteristic operating curves as the basis for machine design under various steady wind conditions. For example, Mazarbhuiya et al 155 investigated a turbine's performance using different asymmetric blades with a focus on the influence of blade aspect ratio whilst specialist facilities enable the breadth of experimentation to be expanded as exemplified by Weber et al 156 who studied turbine noise in the wind tunnel with a 1/2-inch free-field microphones. They showed that the main sources of the H-Darrieus sound pressure field were the separation-stall and the blade vortex interaction.…”
Section: Traditional Wind Tunnel Measurementmentioning
confidence: 99%
“…Figure 5 shows the sound pressure level spectrum for the isolated VAWT at a microphone placed 1 m downstream the axis of the turbine (see Figure 6a for the microphone location). We compare our simulations (black) to experimental data (red), which is extracted from [23]. Comparable experiments for similar VAWT can be found in [22].…”
Section: Aeroacoustic Sources For a Vertical Axis Wind Turbinementioning
confidence: 99%
“…The experiments were performed in the anechoic closed return (with an open test section) wind tunnel at the University of Erlangen-Nurnberg, which has a low turbulence level of 0.15%, see [23] for details. Our simulations use the flow conditions detailed in Table 1, which correspond to the "Full-scale" conditions detailed in [23]. Figure 5a illustrates the good agreement obtained between our simulations and the experiments.…”
Section: Aeroacoustic Sources For a Vertical Axis Wind Turbinementioning
confidence: 99%
“…Both studies indicate lower noise levels compared to HAWTs. The VAWT noise studies based on 2D CFD setups were presented in [16,17], the latter including experimental validation using a small VAWT at very low TSR. In [18], noise predictions using a semi-three-dimensional large-eddy simulation were performed, and [19] used an unsteady three-dimensional (3D) inviscid panel method to predict parts of the noise spectrum.…”
Section: Vawt Noise Predictionmentioning
confidence: 99%